Complex of tasks for monitoring and automatic control of mobile robots for vertical movement = Комплекс задач мониторинга и автоматического управления мобильными роботами для вертикального перемещения - Kozlov, O. V.; Gerasin, O. S.; Kondratenko, G. V.; Козлов, А. В.; Герасин, А. С.; Кондратенко, Г. В. (My University, 2017)
There have been analyzed and formalized the tasks of monitoring and automatic control of mobile robots (MR) for their movement and execution of various types of technological operations on inclined and vertical ferromagnetic surfaces. Generalized structure of a mobile robotic complex is shown with consideration to its main subsystems. The paper presents critical analysis of the current state of the problem of development of universal structures of MRs for the various types of technological operations and elaboration of computerized systems for monitoring and control of MR movement. In particular, there is provided a review of wheeled, walking and tracked MRs with pneumatic, vacuum-propeller, magnetic and magnetically operated clamping devices to grip vertical and ceiling surfaces. The constructive features of the crawler MR with a magnetic clamping device capable of moving along inclined ferromagnetic surfaces are considered. The basic technical parameters of the MR are shown for the further synthesis of computerized monitoring and automatic control systems. Formalization of monitoring and control of the MR positioning at the processing of large ferromagnetic surfaces is considered from the point of view of the control theory = В работе проведен анализ и формализация комплекса задач мониторинга и автоматического управления мобильными роботами (МР) для перемещения и выполнения различных технологических операций на наклонных и вертикальных ферромагнитных поверхностях большой площади. Определены основные управляемые координаты гусеничного МР с магнитными прижимными устройствами для дальнейшего синтеза компьютеризированной системы мониторинга и автоматического управления.
Kozlov, O. V. Complex of tasks for monitoring and automatic control of mobile robots for vertical movement / O. V. Kozlov, O. S. Gerasin, G. V. Kondratenko // Shipbuilding & Marine Infrastructure. – 2017. – № 2(8). – P. 77–87.
Keywords: mobile robot; propulsor; clamping device; control system; positioning; controlled coordinates; мобильный робот; движитель; прижимное устройство; система управления; позиционирование; управляемые координаты